Klebsiella pneumoniae carbapenamases in Escherichia coli isolated from humans and livestock in rural south-western Uganda. - Barbra Tuhamize; Benon B Asiimwe; Kennedy Kasaza; Wilber Sabiiti; Mathew Holden; Joel Bazira (PLoS ONE, 2023)
Background The accumulation of resistance genes in Escherichia coli (E. coli) strains imposes limitations in the therapeutic options available for the treatment of infections caused by E.coli. Production of Klebsiella pneumoniae carbapenemase (KPC) by E. coli renders it resistant to broad-spectrum β-lactam antibiotics. Globally there is existing evidence of spread of carbapenem-resistant E. coli in both humans and livestock driven by acquisition of the several other carbapenemase genes. Overall, there is little information regarding the extent of KPC gene distribution in E. coli. We set out to determine the prevalence, and evaluate the phenotypic and genotypic patterns of KPC in E. coli isolated from humans and their livestock in rural south western Uganda. Methods A laboratory-based, descriptive cross-sectional study was conducted involving 96 human and 96 livestock isolates collected from agro-pastoralist communities in Mbarara district in south western Uganda. Phenotypic and molecular methods (PCR) were used for presence and identification of KPC genes in the E. coli isolates. A chi-square test of independence was used to evaluate the differences in resistant patterns between carbapenems and isolates. Results The overall prevalence of carbapenem resistance by disk diffusion susceptibility testing (DST) for both humans and livestock isolates were 41.7% (80/192). DST-based resistance was identical in both human and livestock isolates (41.7%). The prevalence of carbapenem resistance based on Modified Hodge Test (MHT) was 5% (2/40) and 10% (4/40) for humans and livestock isolates respectively. Both human and livestock isolates, 48.7% (95/192) had the KPC gene, higher than phenotypic expression; 41.7% (80/192). blaKPC gene prevalence was overall similar in human isolates (51%; 49/96) vs livestock isolates (47.9%; 46/96). Approximately, 19% (15/80) of the isolates were phenotypically resistant to carbapenems and over 70% (79/112) of the phenotypically sensitive strains harbored the blaKPC gene. Conclusion Our results suggest that both human and livestock isolates of E. coli in our setting carry the blaKPC gene with a high percentage of strains not actively expressing the blaKPC gene. The finding of fewer isolates carrying the KPC gene than those phenotypically resistant to carbapenems suggests that other mechanisms are playing a role in this phenomenon, calling for further researcher into this phenomenon.